Microstructure Evolution of the Mg-5.8 Zn-0.5 Zr-1.0 Yb Alloy During Homogenization - Li,Lu (2017)
The influence of homogenization treatment on microstructure evolution of Mg-5.8Zn-0.5Zr-1.0Yb (mass fraction, %) alloy was investigated under different annealing temperatures and holding times. Results indicated a severe dendritic segregation in the as-cast ingot. Zn and Yb segregate remarkably at the grain boundary and Zr appears in the form of precipitates. The Mg-Zn binary eutectic phases and a new ternary phase Mg-Zn-Yb are mainly distributed at dendrite boundaries. After homogenization, most of the eutectic phases dissolve into the matrix, except for a small amount of Mg-Zn-Yb phase. The area fractions of residual secondary phase decrease from 5.54% in the as-cast alloy to 0.59% in the well-homogenized sample. Microhardness test indicates that with the increasing temperature and holding time, microhardness value decreased sharply within the first stage of homogenization and then increased steadily to the local maximum value at 380 ºC and 12 h, followed by a slight reduction. Basing on the comprehensive analysis on microstructure and mechanical properties, the homogenization treatment at 380 ºC for 12 h is preferable.